Security and Intelligence Challenges in Guinea-Bissau, Africa’s Narco-State and Issues Beyond Borders - Abiodun, Dr. Temitope Francis; Fajimbola, Dr. Joshua Olatunde (Advances in Social Sciences Research Journal, 2021)
This paper focuses on the international security concerns in relation to the disquiets in the tiny West African state, Guinea-Bissau since independence. The country famously known as “narco-state” faces formidable challenges with weak governance negatively impacting on intelligence services. Intelligence and security reform is a building block of democracy, but this has been habitually weakened in Guinea-Bissau during the last four decades. The state remains one of the most fragile nations in the world having had its security culture totally perturbed, occasioned by the military rule since independence from Portugal in 1974. With over nine coup d’états that have been staged with a number of state administrations toppled coupled with an avalanche of internal conflicts, and prevalence of transnational phenomena (cocaine trafficking), and other traditional state-based challenges, the African narco-state has been left with a very weak governance structure, security, and intelligence services. The study examines Guinea-Bissau’s intelligence culture drawing from secondary sources to understand how intelligence has been shaped and how intelligence has influenced the country in the context of poverty and authoritarianism. The study examines the various factors that have shaped the state’s intelligence, analyzing the transformation and reform in the state’s defense and security sector. It provides recommendations so the Bissau-Guinean intelligence community can be more effective. This study uses secondary sources and makes use of descriptive and content analyses techniques.